Prenatal care with blind pregnant women: validation of an instrument for nurses on knowledge, attitude and practice - Moura Luzia, Francisco Jardsom; Mariano Grimaldi , Monaliza Ribeiro; Cezário Roscoche , Kariane Gomes; Barbosa Carneiro, Josemara; Jardani de Souza Medeiros, Antonia Ellen; Neves da Mota , Liliana Andreia; Correia Barroso Pinto, Cristina Maria; Pinheiro de Oliveira , Paula Marciana (Investigación y Educación en Enfermería, 2025)
Objective. To verify evidence of validity of the instrument “Knowledge, Attitude, and Practice of Nurses in Prenatal Care for Visually Impaired Pregnant Women”. Methods. Methodological study to assess content validity with the participation of 22 expert nurses (11 from the area of Sexual and Reproductive Health and 11 from the area of People with Disabilities). The instrument was adapted into a Google Forms questionnaire and assessed Objectivity, Clarity, and Relevance. The data were analyzed using the Content Validity Coefficient and Content Validity Ratio, in addition to calculating Cronbach's Alpha for internal consistency. Ten generalist nurses from Primary Care participated in the semantic validation, evaluating comprehension, relevance, and possible adjustments to the instrument, with calculation of the Semantic Concordance Index. Results. The instrument obtained an overall Content Validity Coefficient above 0.90 for objectivity, clarity, and relevance, with internal consistency (Cronbach's Alpha = 0.89). The experts' suggestions improved the wording and structure. In semantic validation, the Semantic Concordance Index was 0.97, reinforcing clarity and applicability. Conclusion. The instrument showed evidence of content validity, being objective, clear, and relevant for assessing the Knowledge, Attitude, and Practice of nurses in the prenatal care of pregnant women with visual impairment.